Towards a criminology of public inquiries: From cautious optimism to contestation in the Brook House Inquiry - Schlembach, Raphael (Criminology & criminal justice, 2025)
Although UK public inquiries garner huge amounts of public attention, there have been few systematic studies of their role in scrutinising and reforming criminal justice policy and practice. This is despite a growing number of inquiries, held under the Inquiries Act 2005, into critical matters relating to policing, justice and home affairs. This article explores the contested nature of statutory inquiries as mechanisms for accountability and opportunity for policy reform. We suggest that inquiries provide fertile grounds for criminological analysis, if we understand them as sites of contestation where political priorities compete over questions of procedure, scope and participation. Our focus is on the Brook House Inquiry into the mistreatment of detainees in a British immigration removal centre. The analysis shows a tension between the public-facing nature of inquiries and their legalistic processes.